Mapping the landscape of global programmes to evaluate health interventions in pregnancy: the need for harmonised approaches, standards and tools. Issue 5 (15th October 2018) - Zuber, Patrick L F; Moran, Allisyn C; Chou, Doris; Renaud, Françoise; Halleux, Christine; Peña-Rosas, Juan Pablo; Viswanathan, Kavitha; Lackritz, Eve; Jakob, Robert; Mason, Elizabeth; Lamprianou, Smaragda; Guillard-Maure, Christine
Abstract : Pregnant women and their babies are among the populations most vulnerable to untoward health outcomes. Yet current standards for evaluating health interventions cannot be met during pregnancy because of lack of adequate evidence. The situation is even more concerning in low-income and middle-income countries, where the need for effective interventions is the greatest. Meeting the Sustainable Development Goals for health will require strengthened attention to maternal and child health. In this paper we examine ongoing initiatives aimed at improving the assessment of maternal interventions. We review current methodologies to monitor outcomes of maternal interventions and identify where harmonisation is needed. Based on this analysis we identify settings where different minimal data sets should be considered taking into consideration the clinical realities. Stronger coordination mechanisms and a roadmap to support harmonised monitoring of maternal interventions across programmes and partners, working on improving pregnancy and early childhood health events, will greatly enhance ability to generate evidence-based policies.